2022
DOI: 10.26443/mjm.v20i1.914
|View full text |Cite
|
Sign up to set email alerts
|

Rewarding progress: Effective learning strategies through a variable ratio incentive-based approach in medical education

Abstract: Medical students are faced with many unprecedented challenges, one of which is the large amount of material they are required to learn and retain. While effective learning strategies have been thoroughly researched, stress levels amongst medical students remain very high due to perceived failure to retain material, suggesting that novel methods of implementing such existing strategies are required. Aside from stress levels, additional challenges in medical education include the incorporation of inconsistent te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Accordingly, Hogarth and Villeval (2014) found that intermittent reinforcement leads to higher mean performance and to more persistence in efforts of individuals compared to continuous reinforcement. In addition to this, previous research highlighted that variable ratio schedules suit the classroom setting well (Lee and Belfiore, 1997;Ivy et al, 2017;Rizk et al, 2022). Thus, the persistence of classroom engagement should be higher if it is reinforced through variable ratio schedules.…”
Section: Reviewed Bymentioning
confidence: 94%
“…Accordingly, Hogarth and Villeval (2014) found that intermittent reinforcement leads to higher mean performance and to more persistence in efforts of individuals compared to continuous reinforcement. In addition to this, previous research highlighted that variable ratio schedules suit the classroom setting well (Lee and Belfiore, 1997;Ivy et al, 2017;Rizk et al, 2022). Thus, the persistence of classroom engagement should be higher if it is reinforced through variable ratio schedules.…”
Section: Reviewed Bymentioning
confidence: 94%